Immune reconstitution inflammatory syndrome in treatment-experienced HIV-infected patients - Ramos, Fabiano; Didonet Moro, Ana Lúcia; Rigatto, Maria Helena (Clinical and Biomedical Research, 2014)
We described two cases of treatment-experienced HIV-infected patients who presented with cytomegalovirus uveitis and Cryptococcus neoformans adenitis as a manifestation of immune reconstitution inflammatory syndrome (IRIS) during salvage treatment. Little is known about IRIS in highly experienced patients, and this report suggests that IRIS should be considered in this setting if there is a favorable response to salvage therapy.